Q is for quarry - Grafton, Sue.; Pordage, Vera. (new york : CNIB, 2002)
The 18-year-old murder of an unidentified young woman has never been solved by the Santa Teresa County Sheriff's Department. Two of the original detectives, now elderly and ill, decide to try once more to identify the "Jane Doe" and discover who killed her. Kinsey Millhone agrees to help, little knowing that the old murder will touch on her own past and put her life in danger. Some descriptions of sex and violence, some strong language. 2003.
Vera Pordage.
All Ages.
Keywords: Millhone, Kinsey (Fictitious character) -- Fiction; Women private investigators -- California -- Fiction; Talking books -- 2006.; California -- Fiction; Mystery fiction